Non-Tax State Revenue at the Directorate General of General Legal Administration in the Perspective of State Finance Law - Wulan Kusumaramdhani (IHSA Institute, 2022)
State revenue is part of the scope of State Finance which is divided into tax revenues, Non-Tax State Revenue (PNBP) and grants which are managed in the APBN mechanism. In the management of State Finances, PNBP has two functions, namely the budgeting function and the regulatory function. This study intends to find out how PNBP is managed at the Directorate General of General Legal Administration (DG AHU) in the perspective of state finance law and how PNBP is managed at the DG AHU during the Covid19 Pandemic. The research method used is normative juridical with a statutory approach supported by field studies. In addition, a quantitative approach will be used in the form of descriptive analysis using a statistical approach and effectiveness analysis to determine the management of PNBP at the Directorate General of AHU. The results obtained indicate that based on the regulation regarding the type of PNBP, the Directorate General of AHU has the right to collect PNBP originating from legal services for legal entities, general civil law, notary, inheritance, fiduciary, fingerprint taking for formulation, political parties, citizenship, citizenship status, investigators. Civil Servants, as well as Non-Legal Business Entities. Meanwhile, the management of PNBP at the Directorate General of AHU during the Covid pandemic was able to maintain an effective performance assessment with an effectiveness percentage of 82.54% in 2020 and 83.34% in 2021